Penerapan Problem-Based Learning Berbantuan Media Spinner untuk Meningkatkan Hasil Belajar Siswa Kelas IV pada Mata Pelajaran IPAS - Yuwalina, Nina Ayu Nurma; Jatmiko; Lestari, Dwi Puji (PTK: Jurnal Tindakan Kelas, 2025)
This study is based on the results of observations that show that students' learning scores in science lessons about climate and its changes are still low. This study aims to improve learning outcomes at SDN Pojok 1 in science lessons on climate and its changes using interactive spinner media and using the Problem-Based Learning learning model. This study is PTK for grade IV students, with data from tests and observations analyzed descriptively quantitatively. The findings of this study indicate that learning outcomes related to conceptual understanding of 22 students who took the test, obtained a percentage of 72.72% completion rate in cycle 1 and 95.45% in 22 students in cycle II. It can be concluded that the implementation of the Problem-Based Learning model assisted by spinner media has been proven to improve science learning outcomes. Therefore, the Problem-Based Learning model assisted by spinner media can be the right choice for teachers to make teaching and learning activities more diverse and interesting in the classroom.